Imune à fake news em saúde: o ensino, a formação em Enfermagem e o enfrentamento da desinformação sobre vacinas contra a COVID-19 - Carvalho Junior, Juranildo Alves de (Universidade Federal de São Carlos, 2026)
The COVID-19 pandemic intensified the circulation of misinformation and fake news about vaccines, posing significant challenges to public health and professional education. This study aimed to analyze how fake news related to COVID-19 vaccines are addressed in nursing education and to understand students’ perceptions of their preparedness to confront health misinformation in professional practice. This is a mixed-methods study, conducted with nursing students from a Brazilian public university. Data were collected through a structured questionnaire using Likert-scale items and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, and qualitative data were examined through thematic analysis. The results indicate that students recognize the significant impact of fake news on vaccine hesitancy and express concern about the increase in preventable diseases. However, the findings also reveal that the topic is addressed in a fragmented and unsystematic manner during undergraduate education, with noticeable educational gaps and diverse teaching approaches. The study concludes that addressing vaccine-related misinformation in nursing education requires continuous pedagogical strategies that integrate theoretical foundations, health education, and risk communication, to strengthen professional autonomy and critical practice in the face of contemporary public health challenges.
Immune to fake newns in health: teaching, Nursing education, and confronting misinformation about COVID-19 vaccines
Keywords: Educação em Saúde; Teoria Crítica; COVID-19; Vacinação; Fake News; Health education; Critical theory; COVID-19; Fake news; vaccines; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade